The effectiveness and safety of cranial nerve block in migraine: a critical review - Lee, Annelise Akemi Higa (2023)
Cranial nerve blocks (CNBs) have been used for the acute and preventive treatment of a variety of headaches, including migraine. The effectiveness of CNBs in migraine is usually observed beyond the duration of the nerve block, possibly due to central pain modulation. The most used target is the greater occipital nerve. Other commonly targeted nerves are the lesser occipital nerve and various branches of the trigeminal nerve, including the supratrochlear, supraorbital, and auriculotemporal nerves. CNBs are generally safe and well-tolerated procedures that can be performed in either emergency or outpatient settings. There is currently no guideline standardizing CNBs in migraine. In clinical practice, as well as the few published studies, the results are encouraging, justifying further studies in the area. In the present study we critically review the literature about the safety and efficacy of CNBs in the treatment of migraine attacks and in the preventive treatment of migraine.